2016
DOI: 10.3390/md14080144
|View full text |Cite
|
Sign up to set email alerts
|

High-EPA Biomass from Nannochloropsis salina Cultivated in a Flat-Panel Photo-Bioreactor on a Process Water-Enriched Growth Medium

Abstract: Nannochloropsis salina was grown on a mixture of standard growth media and pre-gasified industrial process water representing effluent from a local biogas plant. The study aimed to investigate the effects of enriched growth media and cultivation time on nutritional composition of Nannochloropsis salina biomass, with a focus on eicosapentaenoic acid (EPA). Variations in fatty acid composition, lipids, protein, amino acids, tocopherols and pigments were studied and results compared to algae cultivated on F/2 med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 45 publications
(135 reference statements)
2
41
0
Order By: Relevance
“…Fatty acid compositions in oil and Bligh and Dyer extracts were determined as described by Safafar, Hass, Møller, Holdt, and Jacobsen () ( n = 2). In brief, 1 g of Bligh and Dyer extract or 0.3 g of oil was weighed in test tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid compositions in oil and Bligh and Dyer extracts were determined as described by Safafar, Hass, Møller, Holdt, and Jacobsen () ( n = 2). In brief, 1 g of Bligh and Dyer extract or 0.3 g of oil was weighed in test tubes.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the cultivation of microalgae so far have focussed mainly on the effects of growth conditions, such as light intensity, temperature, nutrient level, cultivation mode and cultivation-reactor type. [11][12][13][14] Amongst these growth conditions, the rheological properties of microalgal suspensions can affect both transport (transfer effect of nutrients within the suspensions) and downstream processes (harvesting and dewatering). 15 For example, Adesanya et al 16 examined the rheology of microalgal suspensions for biofuel processing and indicated that a scientific understanding of the fluid behavior of microalgal suspensions could promote effective microalgae growth and processing.…”
Section: Introductionmentioning
confidence: 99%
“…17,31,32,33 Generally, the higher the biomass productivity, the higher the EPA productivity. 34,35,36 However, this is not always the case for all species because the lipid content is lower in most cases, as mentioned earlier. Increasing lipid content using a physiological manipulation technique is therefore very important for many species in order to generate the considerable amount of lipids necessary for biofuels production.…”
Section: Sampling and Culture Maintenancementioning
confidence: 88%